ORE MINERALS OF THE BURANOVSKOE TUNGSTEN DEPOSIT (SOUTHERN URALS) - A.V. Kasatkin; A.M. Kuznetsov; N.A. Arzamastsev3 (Минералогия)
Primary and supergene Pb, Bi, Te, Cu, Mo, Ag, Au and Hg minerals are found in samples from the dumps of the Buranovskoe tungsten deposit (Chelyabinsk oblast). The paper presents the most complete list of mineral species of the deposit based on available literature and our data. Fourteen tellurides and sulfotellurides are identified. They occur as individual grains and intergrowths with each other or simple sulfides and form numerous inclusions in fahlores in quartz-scheelite veins. Among the oxidation products of fahlores, galena and tetradymite, we found rare supergene minerals – telluroperite and perite, which form a limited solid solution series, as well as choloalite and a Ag and Hg sulfide-iodide corresponding to hanauerite by its chemical composition. The findings of telluroperite and hitachiite are the first at the territory of the Russian Federation and perite and choloalite are found for the first time in the Urals.